Liposomal butamben gel formulations: toxicity assays and topical anesthesia in an animal model. (2nd January 2017) - Cereda, Cintia Maria Saia; Guilherme, Viviane Aparecida; Alkschbirs, Melissa Inger; de Brito Junior, Rui Barbosa; Tofoli, Giovana Radomille; Franz-Montan, Michelle; de Araujo, Daniele Ribeiro; de Paula, Eneida
Abstract: The aim of this study was to evaluate the in vitro cytotoxicity and the in vivo analgesic effect and local toxicity of the local anesthetic butamben (BTB) encapsulated in conventional or elastic liposomes incorporated in gel formulations. The results showed that both gel formulations of liposomal BTB reduced the cytotoxicity ( p < 0.001; one-way ANOVA/Tukey's test) and increased the topical analgesic effect ( p < 0.05; one-way ANOVA/Tukey's test) of butamben, compared to plain BTB gel. The gel formulations presented good rheological properties, and stability assays detected no differences in physicochemical stability up to 30 d after preparation. Moreover, histological assessment revealed no morphological changes in rat skin after application of any of the gel formulations tested.